2020
DOI: 10.1038/s41598-020-74653-1
|View full text |Cite
|
Sign up to set email alerts
|

Deep learning algorithms for detecting and visualising intussusception on plain abdominal radiography in children: a retrospective multicenter study

Abstract: This study aimed to verify a deep convolutional neural network (CNN) algorithm to detect intussusception in children using a human-annotated data set of plain abdominal X-rays from affected children. From January 2005 to August 2019, 1449 images were collected from plain abdominal X-rays of patients ≤ 6 years old who were diagnosed with intussusception while 9935 images were collected from patients without intussusception from three tertiary academic hospitals (A, B, and C data sets). Single Shot MultiBox Dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 32 publications
(35 reference statements)
0
15
1
Order By: Relevance
“…The first stage is to detect the wrist ROI, then the segmentation model uses this detected wrist ROI as the input image. This cascade system can focus on this ROI and segment ten wrist bones more precisely, which could be helpful for our study, wherein the ROI is a small section of the overall image [ 25 , 26 ].…”
Section: Methodsmentioning
confidence: 99%
“…The first stage is to detect the wrist ROI, then the segmentation model uses this detected wrist ROI as the input image. This cascade system can focus on this ROI and segment ten wrist bones more precisely, which could be helpful for our study, wherein the ROI is a small section of the overall image [ 25 , 26 ].…”
Section: Methodsmentioning
confidence: 99%
“…In recent years, however, studies investigating risk stratification for intussusception in children have demonstrated the utility of abdominal X-rays as an initial diagnostic modality, with one study reporting sensitivity and specificity values of 0.77 and 0.79, respectively [ 29 ]. Unlike ultrasound (US), plain radiography is unaffected by operator skill and equipment variability and remains an inexpensive option for a first-line screening test [ 19 ]. As such, the implementation of AI algorithms in abdominal radiography may have a broad patient impact, and it shows promise as an initial point of entry.…”
Section: Diseases Of the Digestive Tractmentioning
confidence: 99%
“…The sensitivity of the algorithm was higher when compared with radiologist interpretation alone (0.76 vs. 0.46), while there were no significant differences in the specificity (0.96 vs. 0.92) [ 30 ]. More recent studies with larger sample sizes have demonstrated improved detection of intussusception with ranges between 0.91–0.94 and 0.85–0.91, respectively [ 19 ]. Other authors have described similar findings with AUC values of 0.95 and 0.97 and an accuracy of 0.93 and 0.95 [ 19 ].…”
Section: Diseases Of the Digestive Tractmentioning
confidence: 99%
See 1 more Smart Citation
“…Third, there was a difference in resolution between the medical images and the input images due to resizing. Therefore, it is possible for information loss to occur when attempting to detect FNF since the medical images were downsized [35]. Finally, external validation in phase 1, applying the network of trained with single hospital directly to another hospital showed lower accuracy than the results using a single hospital.…”
Section: Limitationsmentioning
confidence: 99%